Sensory Analysis, Caffeine, Chlorogenic Acid and Non-Volatile Taste Compounds of Arabica Coffee (Coffea arabica) Fermented with Sugar Addition for Brew Taste - Kresna Mulya Santosa; Supriyadi Supriyadi; Sri Anggrahini; Yudi Rahmadian (Indonesian Food and Nutrition Progress, 2020)
Arabica coffee is the most popular variety of coffee among the people because it has a more complex flavor than other coffee varieties. This study aims to determine sensory properties and non-volatile components in Arabica coffee fermented with sugar addition. The sensory assessment showed that the best cupping score was the samples fermented with the addition of 0.55% fructose with a total score of 85.25 compared to honey (H) and Fullwash (FW) samples. Fermentation with the addition of 0.55% fructose could produce better coffee compared to samples (H) and (FW). Fermentation with the sugar addition of 0.55% could affect non-volatile components such as soluble sugars, organic acids, amino acids, caffeine, and chlorogenic acid. The content of chlorogenic acid and caffeine analysed by HPLC was found relatively stable in green and roasted beans. Amino acids analysed by LCMS showed glutamate was the highest amino acid in all samples and were supposed to have a role in Maillard reaction contributing to coffee flavor. In conclusion, fermentation with the addition of 0.55% sugar in coffee processing could generally enhance the coffee flavor for brew taste with its potential as functional drink.